Privatization and Firm Performance: a Study of Indonesia’s State-owned Enterprises - Soejono, Fransiska; Heriyanto, Heriyanto (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2018)
This study aimed to examine the differences in the company’s performance before and after privatization. This study also examined the differences in performance before and after privatization on specific sub-samples of the data which is based on privatization method. Government policy of carrying out the privatization toward SOEs is still pro and contra. Various Privatization methods offer its weaknesses and strengths. There are different opinions on the best method for SOE privatization in Indonesia. The population is all companies which execute the privatization method. Secondary data were used namely financial statement which was taken from the Indonesia Stock Exchange, and the company’s website. Data were analyzed using normality test data. In addition, the paired t-test by using normally distributed data assumption was used to test the hypothesis. The results showed that Direct method privatization positive and significant changes in measuring Total Asset Turnover. Performance conducted Privatization through the capital markets showed different results. Test on the capital market method of data showed a similar effect with an analysis on the entire data (without separating the privatization method used) that occur significant performance degradation, especially in measuring Total Asset Turnover, Debt Ratio and Return On Equity. Conducted Management/ Employee Buy-Out (MBO) privatization implied a substantial reduction in measuring Debt Ratio and Return on Equity Performance.